KEHIDUPAN SOSIAL EKONOMI TUKANG TIBO DI KECAMATAN MODOINDING KABUPATEN MINAHASA SELATAN - Chenying Yuriko Suling (Universitas Sam Ratulangi, 2023)
Small traders already exist and grow along with the development of a village or city area, especially in developing countries. Small trade consists of traders who open a simple place to sell that is visited by consumers or traveling merchants who come to their consumers. Small traders in this paper are called tukang Tibo which is one of the alternative jobs done by humans to make ends meet, due to the difficulty of employment available to low-educated members of society with very limited experience and skills. In general, the livelihood of residents in Modoinding District, South Minahasa depends on the agricultural sector, and plantations. The majority of the population pursues work as farmers and the largest income is in the agricultural sector. Modoinding is a sub-district that has abundant natural resource potential. With fertile soil and containing minerals in it, it encourages the community to manage and utilize the culture of these natural resources to grow crops and make the main livelihood, especially horticultural crops so that this village becomes a mainstay of productivity in agriculture. Tukang Tibo or called small traders in Modoinding District is a job supporting market-oriented agricultural activities. They work with various strategies to meet the needs of life. Tukang Tibo in this case, especially in Modoinding District, carries out these activities by going around the plantation to look for plants or plants that are ready to be harvested for purchase or in this case (bought). Keywords: socio economic, small trader, tukang tibo